Decolonisation and a third possibility for the university - Le Grange, L. (South African Journal of Higher Education, 2023)
Decolonisation has recently captured the attention of those who inhabit South African universities, mainly sparked by student protests of 2015 and 2016. In this article writing is used as a mode of inquiry to explore what it means to decolonise the university in a contemporary world that is confronted with crises of all kinds; political, economic, environmental, health, education, and so forth. A third world university is pitted against a first world university (the neoliberal university that accumulates) and a second world university (the university that critiques), not as a new utopian idea but as a university that scavenges on the scrap material of the first and second world universities to retool them for decolonial purposes. In doing so the article changes the angle of vision on decolonising the university in South Africa and elsewhere. The author thinks with la paperson’s ideas including hir notion of scyborg, which refers to people who use their agency to retool material of the first and second world universities to garner decolonial desires. A third possibility for the university jettisons the idea of a totalizing, utopian, decolonised university. What is possible is that the university can operate like a decolonised university, without being disengaged from the first and second world universities, signifying new ways of thinking/doing research, teaching, learning and community engagement. Keywords: critique, decolonial desires, decolonization, neoliberal university, third possibility, scyborg.